Verifikasi Metode Pengujian Kadar Besi (Fe) dalam Asam Klorida Teknis Sesuai SNI 2557-2015 - Fajriani, Atiqah; Beri, Deski (TSAQOFAH, 2026)
Analysis of metal content in industrial chemicals has been widely studied, but research that specifically discusses the verification of the UV-Vis spectrophotometric method in determining iron (Fe) content in technical-grade hydrochloric acid according to national standards remains limited. This study aims to verify the feasibility of the UV-Vis spectrophotometric method in analyzing iron (Fe) content based on method validation parameters. This study employed a quantitative approach with a laboratory experimental design. The research sample consisted of technical-grade hydrochloric acid selected through the purposive sampling technique. Data were collected using a UV-Vis spectrophotometer and supporting laboratory equipment and were then analyzed using linear regression through a calibration curve, as well as testing of precision, accuracy, and recovery parameters. The results show that the method used had very good linearity, with an r² value of 0.9993, precision that met the criterion of %RSD < 2/3 Horwitz CV, and recovery values in the range of 89–104%, which were in accordance with the acceptance standards. These findings indicate that the UV-Vis spectrophotometric method is valid and feasible for use in analyzing iron content in technical-grade hydrochloric acid according to SNI 2557:2015. This study contributes to the development of spectrophotometry-based chemical analysis methods and broadens understanding of method verification in the context of industrial laboratories. The conclusion of the study emphasizes that method validation parameters play an important role in ensuring the accuracy of analytical results. The practical implication is that industrial laboratories need to consistently implement verification procedures to maintain the quality and reliability of testing results.